Calendar Variation Time Series Analysis for Forecasting the Number of Domestic Passengers of Juanda International Airport Surabaya - Putriaji Hendikawati; Anisa Oktaviani (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
This study focuses on forecasting the number of domestic transportation passengers at Juanda International Airport using a time series model by including exogenous variables of calendar variation effects of Eid Al-Fitr and Eid Al-Adha holidays. Data of the number of domestic passengers at Juanda International Airport from the Statistics Indonesia (BDS) was analyzed for the period January 2014 to May 2024. The models used include Dummy Regression, Trend Regression, ARIMA, SARIMA, ARIMAX, and SARIMAX. The analysis results show that the ARIMAX model produces the most accurate prediction. Juanda Airport passenger data is optimal in the ARIMAX ([1,11],1,1) model with the exogenous variable Eid al-Fitr dummy which produces MAPE:7.49; RMSE: 41,133.26; and MAE: 34.119,06. The results of the analysis show that including exogenous variables in the form of calendar variations in the forecasting model can improve prediction accuracy.